Evaluation of performance and emission behaviour of DI diesel engine powered by biofuel. Issue 6 (18th August 2019) - Senthil Kumar, J.; Ramesh Bapu, B. R.; Ganesan, S.; Krishnan, L.
ABSTRACT: In this experiment, the performance, emission, and combustion characteristics of a diesel engine were tested using bio-fuel (Anise oil) at different loads. The main focus of this study was to compare the existing biodiesel blends with the proposed mixture (anise + cerium oxide) of biodiesel blends in terms of engine parameters, cost, efficiency, and pollution control. The blends used in this experiment are B10 (Biodiesel-10%), B20 (Biodiesel-20%), and B30 (Biodiesel-30%). The emission and performance parameters considered for the test are SFC (specific fuel consumption), CO (carbon monoxide), NOX (nitrogen oxide), and HC (hydrocarbon). These parameters were tested for different load conditions such as 0%, 25%, 50%, 75%, and 100%. From the results, it shows that SFC is lower for B20 blend compared to that of pure diesel fuel, while B10, B30, B40, and B50 blends have slightly higher values. From the experiment, it is found that emissions of the HC and NOx were reduced and CO emission is slightly higher than the pure diesel.